2020
DOI: 10.1002/art.41395
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Density Neutrophils in Systemic Lupus Erythematosus

Abstract: Patients with systemic lupus erythematosus ( SLE ) display increased numbers of immature neutrophils in the blood, but the exact role of these immature neutrophils is unclear. Neutrophils that sediment within the peripheral blood mononuclear cell fraction after density centrifugation of blood are generally defined as low‐density neutrophils ( LDN s). Far beyond antimicrobial functions, LDN s are emerging as decision‐shapers during innate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 85 publications
3
40
0
2
Order By: Relevance
“…Since LDN seemed to be more reactive and it has been suggested that LDN in several pathological conditions are prone to release NET (32,47,48), the response of LDN to PMA to form NET was evaluated next. LDN are found among the more abundant MNC, thus in order to appreciate NET formation by LDN alone, these cells were first purified by cell sorting.…”
Section: Low-density Neutrophils Produce Net Similarly To Neutrophilsmentioning
confidence: 99%
“…Since LDN seemed to be more reactive and it has been suggested that LDN in several pathological conditions are prone to release NET (32,47,48), the response of LDN to PMA to form NET was evaluated next. LDN are found among the more abundant MNC, thus in order to appreciate NET formation by LDN alone, these cells were first purified by cell sorting.…”
Section: Low-density Neutrophils Produce Net Similarly To Neutrophilsmentioning
confidence: 99%
“…The hallmark of PMN-MDSCs is their ability to suppress T lymphocyte function [ 14 ]. The most prominent factors implicated in MDSC suppressive activity include increased production of ROS and nitric oxide, upregulation of arginase I and production of prostaglandin E2 [ 15 , 16 ]. Importantly, Basu et al reported a significant correlation between NLR and MDSCs recently [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated neutrophils undergo NETosis to release NETs, a unique form of cell death that is distinct to necrosis and apoptosis [18]. [83,84]. Another related protein is lipocalin-2, an acute phase reactant protein that is found in close association with MMP-9 in the granules of neutrophils [85].…”
Section: Netosis and Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…LL-37); (3) active MMP-9 that mediates endothelial dysfunction [ 80 82 ]. Active MMP-9 is externalized on NETs at significantly higher levels by a distinct proinflammatory subset known as low-density neutrophils [ 82 , 83 ]. Another related protein is lipocalin-2, an acute phase reactant protein that is found in close association with MMP-9 in the granules of neutrophils [ 84 ].…”
Section: Introductionmentioning
confidence: 99%